Cone Beam CT Analysis of Haller Cells: Prevalence and Relationship with Orbital Floor Dehiscence - Mahkameh Moshfeghi; Hamidreza Dehini; Mitra Ghazizadeh Ahsaie (International Journal of Dentistry)
Background and Aim. Haller cells arise from anterior ethmoid air cells and are located in the medial orbital floor, lateral to the maxillary infundibulum. The aim of this cross-sectional study was to determine the prevalence of the Haller cells and its relationship with orbital floor dehiscence on cone beam CT images. Materials and Methods. CBCT images of 120 patients were interpreted in coronal plane for the presence of Haller cells and orbital floor dehiscence. The prevalence of Haller cell, presence of dehiscence, unilateral, or bilateral frequency were assessed. In addition, the size was categorized in three groups of small, medium, and large. Chi-square and Cochran–Mantel–Haenszel tests were used for statistical analysis of the data, and p<0.05 was considered to be significant. Results. A total of 51 male and 69 female with mean ± SD age of 38.84 ± 68.14 were assessed. The overall prevalence of Haller cells was 56.7%, of which 44 (64.7%) were unilateral and 24 were bilateral (35.3%). The majority of the cells (70.7%) were seen in medium (2–4 mm) sized. There was a significant association between Haller cells and orbital floor dehiscence (p≤0.001). Conclusion. The prevalence of Haller cells was remarkably high and the presence of Haller cells was strongly associated with ipsilateral orbital floor dehiscence. Based on the findings of this study, CBCT can be useful in delineation of the bony anatomy of sinonasal complex.